2020
DOI: 10.1017/s0305000919000989
|View full text |Cite
|
Sign up to set email alerts
|

Word learning from context in school-age children: relations with language ability and executive function

Abstract: Purpose: Although school-age children learn most new word meanings from surrounding context, the joint roles of language ability and executive function (EF) in the word learning process remain unclear. This study examined children's acquisition of word meanings from context in relation to oral language ability and three EF skills (working memory, inhibitory control, and cognitive flexibility). Method: Typically developing school-age children completed measures of language and EF, then read and listened to shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 50 publications
0
4
0
1
Order By: Relevance
“…As reviewed earlier, self-regulation facilitates behaviors that make learning more likely, including attention to a teacher, a peer, or a task; impulse control that maintains engagement; monitoring one’s behavior and responses; effort to persist to task completion; and recognition of the need to adjust attention, behavior, or responses accordingly. Elements of executive functioning that undergird self-regulation, such as cognitive flexibility (i.e., the ability to shift thinking between concepts or tasks) are also associated with language development; Hill and Wagovich (2020), for example, observed that preschoolers’ cognitive flexibility, in addition to the prior language skills, were associated with children’s ability to acquire new vocabulary from shared reading activities. Reading instruction and opportunities to read, in turn, provide the basis for further growth and development of language skills that enhance children’s ability to understand and learn from print.…”
Section: The Interactive Relations Among Language and Self-regulationmentioning
confidence: 99%
“…As reviewed earlier, self-regulation facilitates behaviors that make learning more likely, including attention to a teacher, a peer, or a task; impulse control that maintains engagement; monitoring one’s behavior and responses; effort to persist to task completion; and recognition of the need to adjust attention, behavior, or responses accordingly. Elements of executive functioning that undergird self-regulation, such as cognitive flexibility (i.e., the ability to shift thinking between concepts or tasks) are also associated with language development; Hill and Wagovich (2020), for example, observed that preschoolers’ cognitive flexibility, in addition to the prior language skills, were associated with children’s ability to acquire new vocabulary from shared reading activities. Reading instruction and opportunities to read, in turn, provide the basis for further growth and development of language skills that enhance children’s ability to understand and learn from print.…”
Section: The Interactive Relations Among Language and Self-regulationmentioning
confidence: 99%
“…Through language research we have gained an understanding of internal and external factors that affect a child's ability to learn and refine word forms, meanings, and their links during the slow mapping process. Specifically, child‐level factors that are positively related to word learning in quiet environments include, but are not limited to, verbal working memory skills, current vocabulary knowledge, and executive function skills (e.g., Archibald, 2017; Gordon et al, 2022; Kapa & Erikson, 2020; Wagovich, 2020). We also have gained an understanding of external factors that support word learning such as visual cues (e.g., adult eye gaze, Cetincelik et al, 2021), contingent responsiveness of conversation partners (Roseberry et al, 2014), and the timing of form and object presentations (Clerkin & Smith, 2022; Yu & Smith, 2011).…”
Section: Language Sciencesmentioning
confidence: 99%
“…Foreign language education is necessary for all people in order to raise awareness in many areas such as social, cultural, scientific and economic (Garfinkel, Allen, & Neuharth-Prtichett, 1993) According to literature, there is a close relationship between language abilities and the learning ability (Hayes, 1998;Marantika;Swaminathan, 2020;Hill and Wagovich, 2020). Verbally gifted individuals can use language more creatively because they have superior language skills and developed language repositories (Allen, 1992;Gubbels et al, 2018).…”
Section: Introductionmentioning
confidence: 99%